A Novel Platform for Integrating 360° Videos Within a Virtual Study Abroad Experience (Asian Education Studies, 2021)
The rising popularity of high-immersion media has found its way to educational use cases, but such media have not yet been extensively evaluated in their ability to provide fully featured study abroad experiences. As recent events have catapulted virtual study abroad programs to the forefront, and as universities seek to build attractive and effective programs, the necessity of systems that provide immersion and student engagement has become apparent. Using the new concept of Dual-Frame System Design, this paper seeks to find if design thinking methodologies can meet these needs while maintaining system reliability, flexibility, and ease of use. Using off-the-shelf components, including a 360° video camera, smartphones, and personal computers, a system was created and tested through a mixed-methods approach based on a user study of 25 US college students. The results of this research may be useful in the creation of high-immersion virtual study abroad experiences, as well as advancing the interdisciplinary frameworks necessary to make these systems broadly available.